Sudden cardiac death in heart failure. A 20 years perspective from a Mediterranean cohort. (3rd October 2022) - Codina Verdaguer, P; Zamora, E; Levy, W C; Domingo, M; Santiago-Vacas, E; Cediel, G; Santesmases, J; Ruiz-Cueto, M; Diez-Quevedo, C; Roig, T; Troya, M I; Casquete, D; et al.
Abstract: Background: Although sudden cardiac death (SCD) has progressively decreased in the last decade, it remains an important cause of death in patients with heart failure (HF). Differences based on clinical management and regional characteristics might be important. Purpose: To assess the prevalence of SCD along 20 years of study in HF outpatients of different aetiologies managed in a multidisciplinary HF Clinic, and compare this prevalence with the expected proportional occurrence according to the acknowledged Seattle Proportional Risk Model (SPRM) score. Methods: In a prospective observational registry of real-life HF outpatients, modes of death were classified as SCD (any unexpected death, witnessed or not, of a previously stable patient with no evidence of worsening HF or any other known cause of death) and non-SCD (progression of HF, acute myocardial infarction, stroke, procedural, other cardiovascular causes and non-cardiovascular). Results: From August 2001 to May 2021, 2772 outpatients with known cause of death and with SPRM score available were included. Out of them, 1351 (48.7%) died during a median follow-up of 3.8 years [IQR 1.6–7.8], up to 20 years. Observed prevalence of SCD in the 1351 dead patients was 13.6% while predicted SPRM prevalence was 39.6%. Annual SPRM predicted SCD mortality rate was 3.0% while observed SCD annual mortality rate was 1.3%. Figure 1 depicts cumulative incidence of causes of death through the study period. A lower prevalence of SCD was observed in every quintile of SPRM risk (Figure 2). This lower prevalence of SCD was observed independently of left ventricular ejection fraction group, ischemic or non-ischaemic aetiology and implantable cardiac defibrillator (ICD). Although the baseline SPRM predicted risk of SCD showed a significant decreasing trend (p=0.005) along the periods of admission at the Unit, the lower observed prevalence of SCD was seen in all periods of admission. Conclusions: The prevalence of SCD through a perspective of 20 years in a Mediterranean HF outpatient cohort managed in a multidisciplinary HF Clinic was significantly lower than that expected according to the SPRM independently of degree of predicted risk, ischaemic aetiology, period of admission and implanted ICD. Regional lifestyle and dietary habits may have an impact on the lower rate of SCD in this Mediterranean cohort, and deserve further in-depth analyses. Funding Acknowledgement: Type of funding sources: None.